Trait-matching and mass effect determine the functional response of herbivore communities to land-use intensification - Luca Borger (Functional Ecology, 2017)
Trait-based approaches represent a promising way to understand how trophic interactions shape animal communities. The approach relies on the identification of the traits that mediate the linkages between adjacent trophic levels, i.e. ‘trait-matching’. Yet, how trait-matching explains the abundance and diversity of animal communities has been barely explored. This question may be particularly critical in the context of land-use intensification, currently threatening biodiversity and associated ecosystem services. We collected a large dataset on plant and grasshopper traits from communities living in 204 grasslands, in an intensively managed agricultural landscape. We used a multi-trait approach to quantify the relative contributions of trait-matching and land-use intensification acting at both local and landscape scales on grasshopper functional diversity. We considered two key independent functional traits: incisor strength and body size of grasshopper species. Incisor strength, a resource-acquisition trait, strongly matches grasshopper feeding niche. Body size correlates with mobility traits, and may determine grasshopper dispersal abilities. Plant functional diversity positively impacted the diversity of grasshopper resource-acquisition traits, according to the degree of trait-matching observed between plants and herbivores. However, this positive effect was significantly higher in old grasslands. In addition, the presence of specific habitats in the landscape (i.e. wood and alfalfa) strongly enhanced grasshopper resource-acquisition trait diversity in the focal grassland. Finally, grasshopper body size increased with landscape simplification, although the response was modulated by local factors such as soil depth. Trait-matching between plants and herbivores was an important driver explaining the abundance and diversity of resource-acquisition traits within grasshopper communities. However, the presence of specific habitats in the surrounding landscape had also a strong influence on herbivore functional diversity in grasslands. Our study suggests that also mass effects are a central mechanism promoting higher functional diversity within animal communities in highly disturbed anthropogenic systems.